Face-down posturing after macular hole surgery: a meta-analysis. Issue 5 (18th September 2009) - Tatham, Andrew; Banerjee, Somnath
Abstract : Aims: To assess the effect that the duration of face-down posturing has on the outcome of macular hole surgery. Methods: A literature search was conducted to identify studies related to posturing duration following macular hole surgery. Where appropriate, studies were compared in a meta-analysis. The Mantel–Haenszel fixed-effect method was used to calculate the summary statistics. The main outcome measures were macular hole closure rate and visual acuity improvement. Results: 17 studies investigating the effect of face-down posturing time on the outcome of macular hole surgery were identified. 9 studies included a comparison group and were deemed suitable for inclusion in the meta-analysis. Studies were divided into two groups depending on the duration of face-down posturing investigated. The meta-analysis revealed an RR of anatomical failure of 1.34 (95% CI 0.66 to 2.72) with face-down posturing for 24 h or less compared with face-down posturing for 5–10 days, but this was not statistically significant (p=0.42). The study design was too dissimilar to allow a meaningful comparison of visual acuity outcomes. Conclusions: Currently there is insufficient evidence to allow firm conclusions as to whether face-down posturing following macular hole surgery influences hole closure rates. Meta-analyses are limited by the quality of included studies; a well-conducted randomised control trial is needed.